Human and gut microbiota synergy in a metabolically active superorganism: a cardiovascular perspective - Russo, Matteo Antonio; Puccetti, Matteo; Costantini, Claudio; Giovagnoli, Stefano; Ricci, Maurizio; Garaci, Enrico; Romani, Luigina (Frontiers in Cardiovascular Medicine, 2024)
Despite significant advances in diagnosis and treatment over recent decades, cardiovascular disease (CVD) remains one of the leading causes of morbidity and mortality in Western countries. This persistent burden is partly due to the incomplete understanding of fundamental pathogenic mechanisms, which limits the effectiveness of current therapeutic interventions. In this context, recent evidence highlights the pivotal role of immuno-inflammatory activation by the gut microbiome in influencing cardiovascular disorders, potentially opening new therapeutic avenues. Indeed, while atherosclerosis has been established as a chronic inflammatory disease of the arterial wall, accumulating data suggest that immune system regulation and anti-inflammatory pathways mediated by gut microbiota metabolites play a crucial role in a range of CVDs, including heart failure, pericardial disease, arrhythmias, and cardiomyopathies. Of particular interest is the emerging understanding of how tryptophan metabolism-by both host and microbiota-converges on the Aryl hydrocarbon Receptor (AhR), a key regulator of immune homeostasis. This review seeks to enhance our understanding of the role of the immune system and inflammation in CVD, with a focus on how gut microbiome-derived tryptophan metabolites, such as indoles and their derivatives, contribute to cardioimmunopathology. By exploring these mechanisms, we aim to facilitate the development of novel, microbiome-centered strategies for combating CVD. which immune cells and molecules contribute to both the pathogenesis and resolution of cardiovascular diseases (CVD) (Wong et al., 2022). By uncovering these interactions, scientists hope to develop new strategies for preventing and treating cardiovascular conditions through targeted immunomodulatory therapies (Galajda et al., 2024).Cardioimmunology, indeed, is a relatively new and rapidly growing field that focuses on the intersection of CVD and the immune system (Swirski and Nahrendorf, 2018). It explores the complex interactions between the immune system and the cardiovascular system, as well as the role of inflammation in the development and progression of various cardiovascular conditions (Lazzerini et al., 2019, Russo et al., 2023). In the last decade, the systemic dimension has emerged as a predictor of CVD, alongside cardiomyopathies and arrhythmias. Immunomodulation in the local microenvironment, metabolism and mitochondria of the cardiac tissue are highly responsive to the environment (